The study on factors that influence awareness among the customers of Utusan Malaysia digital newspaper / Nur Habibah Najwa Abidin and Wan Muhammad Syahmi Wan Mohd Sabri - Abidin, Nur Habibah Najwa; Wan Mohd Sabri, Wan Muhammad Syahmi (2013)
In recent years, the development of the Internet has affected the way in which most business work. Newspaper publishing is one of the activities that have been more affected by the development of the Internet. In fact, the appearance of the new digital media has implied important changes in this sector. Some newspaper company grabs the opportunities by introducing digital newspaper. In an attempt to understand how consumers aware about the concepts of digital newspaper, this study seeks to explore the factors that influence awareness among the customer of Utusan Malaysia digital newspaper. In addition, this study also aims to find the relationship between dependent and independent variables. A study of 100 consumers of Utusan Malaysia digital newspaper shows that web site’s usability, reputation, familiarity and privacy are all significant and have relationships with awareness among the customer of Utusan Malaysia digital newspaper.